Factors Affecting Audit Report Lag in Property And Real Estate Companies On The IDX 2017-2021 - Indah Lia Puspita; Riska Putri Sabrina (Komunitas Dosen Indonesia, 2024)
Issuers listed on the stock exchange are mandated by Regulation No. 29/PJOKK.04/2016, issued by the Financial Services Authority (OJK), to submit their annual reports by the conclusion of the fourth month following the end of the financial year. However, there remains a deficiency in awareness regarding this obligation among entities, particularly concerning the reporting of audited financial statements. As reported by www.kontan.co.id (2023) the Indonesian Stock Exchange (BEI) revealed recently that sixty-one listed companies have not submitted audited financial reports by December 31, 2022, as required by law. As a result, they were fined IDR 50,000,000 for the delay and issued a level II written warning. Twelve of these businesses are involved in the real estate and property industry. The purpose of this study is to look at the elements that affect this industry's audit report delays. With the help of purposive sampling, 15 companies were chosen as research samples for the study, which focuses on real estate and property companies listed on the IDX. Multiple linear regression analysis was used to assess hypotheses after secondary data analysis. The findings suggest that although the age of the company and profitability influence audit report delays, the complexity of the company's operations and debt do not have a significant impact on these delays.